ANALISIS KEMAMPUAN IMAJINASI DAN DIKSI DALAM MENULIS PUISI BEBAS PADA MURID KELAS VIII-4 SMPN 2 SELONG - Inda Chairunissa, Baiq; Hary Murcahyanto; Rohayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the imagination and diction abilities of Grade VIII.4 students at SMPN 2 Selong in writing free verse poetry. The research employed a quantitative descriptive approach involving 32 students as the research subjects. Data were collected through a poetry writing performance test and an assessment rubric focusing on imagination and diction. The data were analyzed using descriptive statistical techniques by calculating students' scores and classifying them into achievement categories. The findings revealed that students' abilities in imagination and diction were generally good. Seventeen students (53.13%) were categorized as very good, twelve students (37.50%) as good, and three students (9.37%) as fair. The results indicate that most students were able to express imaginative ideas creatively and select appropriate diction to strengthen the meaning and aesthetic value of their poems. Therefore, students' imagination and diction abilities in writing free verse poetry can be categorized as good and should continue to be improved through continuous writing practice and creative learning activities.